IS REINSTATEMENT POSSIBLE IN CASES OF EMPLOYMENT TERMINATION BASED ON INADEQUATE WORK PERFORMANCE OR INSUFFICIENT KNOWLEDGE AND SKILLS REQUIRED FOR THE POSITION? - Tošić, Miodraga (Glasnik Advokatske komore Vojvodine, 2026)
Researching this theme we have found the practical requirement to distinguish the cancellation of an employment contract due to failure to fulfil work results from the lack of knowledge and capacity as two reasons of dismissal, and also the lack of legal practice make efficient realization of the right to protection especially difficult from unjustified dismissal. In these terms, we have indicated that legal determination and objectivity of work normative contribute to the prevention of the abuse of the right to the cancellation of an employment contract due to failure to fulfil work results and the lack of knowledge and capacity for work, that the introduction of legal obligation of establishing criteria and authority for evaluation of employees knowledge and capacity contributes to greater legal security in the area of the protection from unjustified dismissal whereas more complex dismissal process can have a significanr role in the prevention of labour disputes concerning. We also pointed out that the existing legislative solutions face significant criticism, as they cannot be the same for all reasons for dismissal, and we have realized that reintegration has no practical significance in this particular case of dismissal.